Financial Risk and Opportunities to Build Resilience in Europe - World Bank (World Bank, Washington, DC, 2021)
This report presents an analysis conducted by the World Bank to assess macro-fiscal impacts of earthquakes and floods in European Union (EU) Member States (MS), analyze the financial instruments in place to manage this risk and identify any associated funding gaps. The analysis is underpinned by the outputs of two regionally consistent probabilistic catastrophe risk models, one developed by JBA Risk Management (JBA) for fluvial and surface water flood, and one by the Global Earthquake Model Foundation (GEM) for seismic risk. The report provides, (i) an indication of future losses for each country; (ii) an indication of each countries funding gap based upon the information available on national and EU level financial instruments; and (iii) options for consideration to strengthen financial resilience at the EU and the national level. Overall, this report finds that financial instruments to manage disaster risk are limited in most of the countries and at the EU level, despite the devastating impacts disasters pose to welfare, fiscal balance, and more broadly the economy.